Architectonics in Bakhtin: a look on a course materials for the teaching of Portuguese (Filologia e Linguística Portuguesa, 2012)
The objective of this text is to examine proposals for a coursebook of Portuguese language for high school students, based on the reading of verb-visual texts. Supported by the concepts of “text” and “architectonics” from the theory of Bakhtin and the Circle, and considering how the study of language seeks to understand the production of meaning in a cultural, social and historical dimension, we discuss the orientation given to the written production of publicity texts. The theoretical and methodological approaches used in the didactic sequences allow the students to articulate different texts, verbal and visual, so that they can assume an ethical position in the real world.